1984
DOI: 10.1002/1097-0142(19840615)53:12<2701::aid-cncr2820531224>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma diagnostic and prognostic features in north american patients

Abstract: Diagnostic and prognostic characteristics of 121 North American patients with hepatocellular carcinoma seen in one metropolitan area over a 6‐year period were assessed using multivariate analysis. Presenting symptoms commonly included abdominal pain (53%) or mass (34%), anorexia (31%), and ascites (20%); however, the ability to make an early diagnosis was complicated by a variety of unusual symptoms accounting for 25% of presentations. While cirrhosis (63%) and hepatitis B surface antigen (HBsAg) positivity (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
4
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 33 publications
7
47
4
1
Order By: Relevance
“…For example, a study from 4 hospitals in Los Angeles, CA reported an overall median survival of 18 months among 121 patients with HCC who were seen between 1976 and 1982. 10 On the other hand, previous non-US population-based studies showed similar results. A recent European study reported survival rates from populationbased cancer registries in 17 European countries.…”
Section: Discussionsupporting
confidence: 59%
“…For example, a study from 4 hospitals in Los Angeles, CA reported an overall median survival of 18 months among 121 patients with HCC who were seen between 1976 and 1982. 10 On the other hand, previous non-US population-based studies showed similar results. A recent European study reported survival rates from populationbased cancer registries in 17 European countries.…”
Section: Discussionsupporting
confidence: 59%
“…The relative frequency of HCC in this region is higher than reported from any other part of Saudi Arabia and is many times higher than that seen in Europe and North America. 16 Our figures are closer to those seen in parts of Africa, China and Taiwan, where HCC is the most common malignant tumor. 17 In our study, HCC in Gizan Province showed a male:female ratio of 3.4:1.…”
Section: Discussionsupporting
confidence: 50%
“…A similar conclusion was derived from two recently published series. 26,29 While the model predicts that a high bilirubin level independently influences survival, it might indirectly affect the outcome by restricting the administration of the full dose of doxorubicin, the most active single agent for HCC. 18 A high LDH level above 300 U/L was associated with an accelerated death rate, probably indicating a large tumor burden.…”
Section: Discussionmentioning
confidence: 99%